(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
LED lighting technology dominates the lighting market due to its long operational lifetime and excellent luminous efficiency compared to conventional light sources. Nowadays, several DC-DC SEPIC LED drivers have been presented because of the ongoing advancements in SEPIC and LED. However, the traditional SEPIC has several disadvantages: higher output current and voltage ripple, lower efficiency, and transferring all its energy with a higher capacitance value through the series capacitor. Therefore, this work deals with DC-DC SEPIC-based resonant converters with valley-fill circuits (Vfc). The proposed Vfc helps decrease the switch’s current and voltage stress, increasing LED voltage and current ripple and enhancing efficiency. Therefore, a new resonant DC-DC SEPIC integrated Vfc is discussed in this work. The switch’s current stress, voltage stress, LED voltage ripple, current ripple, and efficiency are evaluated, and these functional parameters are compared to the traditional SEPIC topology. As a result, a unique resonant DC-DC SEPIC integrated Vfc LED driver is developed with an efficiency of 95.6 %. MATLAB/Simulink has been used to simulate the designed circuit for the suggested topologies. A hardware prototype is created, and the results are validated.